PLANEJAMENTO AGROPECUÁRIO MUNICIPAL: A EXPERIÊNCIA DE PINHEIRO-MA - Calegar, Geraldo Magela; Souza, Renival Alves de; Araújo, Pedro Candóia de; Pereira, Nilo Sérgio de Carvalho (Revista Econômica do Nordeste, 1989)
ACERVO HISTORICO